The effect of intravenous ferric carboxymaltose on red cell distribution width: a subanalysis of the FAIR‐HF study. (July 2013) - Van Craenenbroeck, Emeline M.; Conraads, Viviane M.; Greenlaw, Nicola; Gaudesius, Giedrius; Mori, Claudio; Ponikowski, Piotr; Anker, Stefan D.
<x xml:space="preserve">Abstract</x> Aims Red cell distribution width (RDW), a measure of variability in red blood cell size, is a novel prognostic marker in chronic heart failure (CHF). Iron deficiency contributes to elevated RDW. In the FAIR‐HF trial, i.v. ferric carboxymaltose (FCM) improved the 6 min walk test (6MWT) distance in iron‐deficient CHF patients. We studied the effect of FCM on RDW and the relationship between RDW and 6MWT distance. Methods and results In FAIR‐HF, iron‐deficient CHF patients were randomized to FCM or placebo in a 2:1 ratio. From the total cohort (n = 459), we included 415 patients in whom RDW values and 6MWT distance were available for baseline and at least one follow‐up visit (after 4, 12, and 24 weeks). Baseline RDW was higher in anaemic (haemoglobin <12 g/dL) compared with non‐anaemic patients [15.2% (14.0–16.8) vs. 14.2% (13.4–15.4), P < 0.0001, median (interquartile range)]. In multivariate analysis, RDW was significantly associated with transferrin saturation (P < 0.001) and C‐reactive protein levels (P = 0.002). Treatment with FCM led to a biphasic response; RDW increased within 4 weeks (+0.54% absolute change from baseline, P = 0.01) but fell to values below the placebo group after 24 weeks (–1.0 %, P = 0.03). The 6MWT distance and RDW were inversely related at baseline (r = –0.30, P < 0.0001). In all patients, the increase in 6MWT distance after 24 weeks was significantly correlated with a decrease in RDW (r= –0.25, P < 0.0001), even after adjustment for changes in haemoglobin. Conclusions Iron deficiency in CHF is associated with high RDW, even after adjustment for the presence of anaemia. Treatment with i.v. FCM in iron‐deficient CHF patients decreases RDW.